1983
DOI: 10.1046/j.1537-2995.1983.23483276869.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of rabbit red cells for adsorption of cold autoagglutinins

Abstract: This study investigated the use of formaldehyde-fixed rabbit red cells and rabbit red cell stroma for the adsorption of cold autoagglutinins. Both methods were equally effective and removed all antibody activity at room temperature in 92 percent of the samples. However, some alloantibodies such as anti-D, -E, and -Leb were also reduced in titer or completely absorbed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The cause of the misidentification of that example of anti‐Vel as a cold antibody was inappropriate use of prewarming technique. Caution about use of rabbit RBCs for adsorption has also been reported by Waligora and Edwards 11 regarding examples of anti‐D, ‐E, and ‐Le b .…”
Section: Discussionmentioning
confidence: 85%
“…The cause of the misidentification of that example of anti‐Vel as a cold antibody was inappropriate use of prewarming technique. Caution about use of rabbit RBCs for adsorption has also been reported by Waligora and Edwards 11 regarding examples of anti‐D, ‐E, and ‐Le b .…”
Section: Discussionmentioning
confidence: 85%
“…Review of the literature showed that Waligora and Edwards 4 were the first to report the apparent removal of alloantibodies (anti‐D and ‐E) by formaldehyde‐fixed rabbit RBCs in 1983. In contrast, Weiland 17 reported subsequently that 48 examples of anti‐D and 25 examples of anti‐E showed no decrease in reaction strength after RESt adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, prewarming may not abolish the reactivity of cold autoantibodies with high thermal amplitude and may diminish the reactivity of some alloantibodies 2 . Alternatively, cold autoantibodies can be adsorbed from serum with formaldehyde‐fixed rabbit RBCs or RBC stroma, which is also available as a commercial reagent (RESt, Immucor, Norcross, GA) 3‐5 . The mechanism of the adsorption is not known, but it has been proposed that because cold autoantibodies most often have anti‐I or ‐IH specificity, and rabbit RBCs have a greater amount of I antigen than human adult RBCs, cold autoantibodies are thus efficiently adsorbed by rabbit RBCs 6 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Marks and colleagues 1 demonstrated that formaldehyde‐fixed rabbit RBCs were a useful reagent for the adsorption of cold “autoagglutinins,” directed at carbohydrate antigens such as I and IH, and could be used to remove these antibodies without reducing the reactivity of alloantibodies. Another study that used both fixed whole RBCs and rabbit RBC stroma demonstrated similar adsorption of anti‐I and anti‐IH but also observed that some examples of anti‐D, anti‐E, and anti‐Le b were also adsorbed 2 . Antibodies to the Vel blood group antigen are unusual in that they are often a mixture of IgM and IgG and have a wide thermal range.…”
Section: Reactivity Of Anti‐vel Adsorbed With Rest™mentioning
confidence: 95%